2009
DOI: 10.1523/jneurosci.5951-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Ensheathing Glia Function as Phagocytes in the AdultDrosophilaBrain

Abstract: The mammalian brain contains many subtypes of glia that vary in their morphologies, gene expression profiles, and functional roles; however, the functional diversity of glia in the adult Drosophila brain remains poorly defined. Here we define the diversity of glial subtypes that exist in the adult Drosophila brain, show they bear striking similarity to mammalian brain glia, and identify the major phagocytic cell type responsible for engulfing degenerating axons after acute axotomy. We find that neuropil region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
464
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(481 citation statements)
references
References 31 publications
16
464
1
Order By: Relevance
“…Levine (University of Arizona). The alrm-GAL4 (Doherty et al, 2009) flies used to drive expression of Green Fluorescent Protein (GFP) in Drosophila astrocytes were a gift from M Freeman (University of Massachusetts). For D42>ChR2-H134R experiments, homozygous animals were used to achieve sufficient expression and subsequent depolarization to trigger neuronal action potentials.…”
Section: Transgenic Fliesmentioning
confidence: 99%
See 1 more Smart Citation
“…Levine (University of Arizona). The alrm-GAL4 (Doherty et al, 2009) flies used to drive expression of Green Fluorescent Protein (GFP) in Drosophila astrocytes were a gift from M Freeman (University of Massachusetts). For D42>ChR2-H134R experiments, homozygous animals were used to achieve sufficient expression and subsequent depolarization to trigger neuronal action potentials.…”
Section: Transgenic Fliesmentioning
confidence: 99%
“…Fasciclin II-positive axon tracts (magenta) are shown to provide landmarks within the larval VNC neuropil (Landgraf et al, 2003). Drosophila astrocytes were labeled by using the astrocyte-specific driver, alrm-GAL4, to express membrane-targeted GFP (Doherty et al, 2009). In the cross-sectional view of the third thoracic segment in Figure 1A, the cell bodies of 3 of the 12 astrocytes residing in that segment are visible; dorsal (d), lateral (l), and ventral (v) astrocyte cell bodies appear in the left hemisegment.…”
Section: Identification and Intrinsic Properties Of Third-instar Larvmentioning
confidence: 99%
“…Ensheathing glia are the primary cell type in the Drosophila neuropil that express molecular components of the engulfment machinery, including the Draper receptor and dCed-6 adaptor molecule, and they phagocytose axonal debris after axotomy. 19 To determine whether Bsk functions in ensheathing glia, we drove the expression of bsk RNAi or UAS-puc with the ensheathing glia-specific driver mz0709-Gal4 and assayed glial clearance of degenerating axons. We found that suppression of dJNK signaling in ensheathing glia was sufficient to block the glial engulfment function (Figures 2c and d).…”
Section: Rnai104569mentioning
confidence: 99%
“…All strains were obtained from the Bloomington Stock Center or the Vienna Drosophila Resource Center. NP6520-Gal4, NP577-Gal4, and Alrm-Gal4 were gifts from R. Jackson and M. Freeman [21,22]. All fly crosses were carried out at 25°C under standard laboratory conditions unless noted otherwise.…”
Section: Fly Strainsmentioning
confidence: 99%